Livelihoods and Welfare: Findings from the sixth round of the Myanmar Household Welfare Survey (June – November 2023) - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
The sixth round of the Myanmar Household Welfare Survey (MHWS), a nationally and regionally representative phone survey, was implemented between the end of August and November 2023. It follows five rounds that were carried out since the beginning of December 2021. This report discusses the findings from the sixth round related to livelihoods and welfare dynamics. The main findings are the following: 1. Nationally, median real household income per adult equivalent declined by 15 percent between late 2022 and late 2023, indicating that the purchasing power of household income declined substantially over the previous year. Between late 2022 and late 2023, median real income per adult equivalent earned from farm wages increased slightly while real income earned from all other sources stagnated or declined. 2. In late 2023, 13 percent of households had at least one jobless household member who in the three months before the survey spent at least one month seeking income generating work without finding it. The share of households with an unemployed member decreases by asset class (15 percent in asset poor households compared to 8 percent in asset rich households). Four percent of households had a child aged 5–11 who was employed at least one hour in any week in the three months before the survey and 8 percent of households had a child aged 12–14 who was employed at least 14 hours in any week during that period. 3. Between late 2022 and 2023, there has been an overall reduction in household engagement in income earning activities. Except for other income sources (e.g., rent, remittances, and other forms of assistance), the share of households engaged in each income generating activity either declined or increased by a small, statistically insignificant amount. 4. In every state/region, income poverty reached a new high in the period of August–November 2023 compared to all previous MHWS rounds in the last two years. Adjusted in accordance with food inflation, the poverty line increased by 35 percent between late 2022 and late 2023. A failure of nominal income to keep pace with this large jump in the poverty line led to an increase in the percentage of the population living in income-poor households by 17 percent from 62 percent in February–June 2023 to 72 in August–November 2023. 5. Casual wage earning households continue to be the poorest livelihood group with income poverty rates of 90 and 84 percent in farm and non-farm wage earning households, respectively. Nonetheless, income poverty rose to 63 and 67 percent in households whose primary livelihoods are non-farm salary work and non-farm businesses—23 and 17 percent higher than a similar period in the previous year. Finally, over the same period, income poverty increased by 11 percent in farm households to 69 percent. 6. Remittance income is an important stabilizing force. There are only a few factors helping households stay out of poverty, including earning income from salaried employment, migrating with the whole household, and receiving remittances. Individuals living in remittance receiving households are about 22 percentage points less poor compared to individuals in non-remittance receiving households. Households mainly reliant on ‘other’ forms of income, particularly remittances, are the most resilient livelihood group with poverty rates not changing between late 2022 and late 2023. 7. In late 2023, households in Chin, Kayah, Rakhine, Sagaing, and Tanintharyi struggled most of all regions/states with income poverty, unemployment, and challenges to earning income. During that period, poverty headcounts were 93 percent in Chin, 87 percent in Kayah; and around 80 percent in Rakhine, Sagaing, and Tanintharyi. In Kayah, 49 percent of households reported a loss of employment in June–November 2023, while in Tanintharyi 39 percent of households reported a loss of employment. Further, nearly 30 percent of households in Kayah had an unemployed member—more than double the national average. Chin and Rakhine also had a large share of households with unemployed members. Finally, households in Chin were nearly twice as likely as other parts of the country to have employed children—children aged 5–11 were employed in 7 percent of households and children aged 12–14 were employed in 15 percent of households.